THE MAN BY TAYLOR SWIFT: A VISUAL AND LYRICAL CRITIQUE OF GENDER INEQUALITY - Wijaya, Debi Pangestuti (Serat: Journal of Literary & Cultural Studies, 2025)
Taylor Swift’s song and music video “The Man” explicitly highlight gender-based double standards, offering a bold critique of systemic inequality through visual and lyrical storytelling. The work presents a clear commentary on how women are perceived and treated differently from men in professional, social, and cultural settings. “The Man” offers an image through which to look at and comprehend these gaps through her lyrics and music video. The purpose of this study is to identify and analyse gender inequality issues in the lyrics and music video of “The Man”. This study examines the lyrics and music video using a qualitative content analysis approach to identify basic themes and messages about gender inequality through the narrative and symbolism of the song, aiming to reveal both explicit and implicit messages on gender inequality. By analyzing the lyrics and music video, this study uncovers insights into current gender inequality and the double standards prevalent in modern times. Additionally, "The Man" also highlights the ongoing struggle for gender equality and female empowerment.